2017
DOI: 10.1504/ijtel.2017.084069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of concept map approach on students' attitude and motivation towards documenting computing capstone projects

Abstract: Given their importance in assessing the objectives of computing programs, capstone projects have been included in the present curriculum. Through these projects, the issues in software development practice are directly experienced by the students. This paper provided students with a full picture of these issues by using concept maps. To present a comprehensive rubricbased documentation of this project, this paper employs a conceptual map instructional approach and finds a significant overlap between the manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The results are aligned with previous research that showed that a concept mapping approach to teaching enhanced students' attitudes toward conducting projects in the information technology field (Al-Dmour et al, 2017). In addition, the results are aligned with previous research that has shown that a concept mapping approach can enhance students' attitudes toward learning different topics in different fields including circular and rotational motion in physics (Luchembe et al, 2017), and vocabulary acquisition in language learning (Khoshsima et al, 2016).…”
Section: Participants' Attitudessupporting
confidence: 87%
See 2 more Smart Citations
“…The results are aligned with previous research that showed that a concept mapping approach to teaching enhanced students' attitudes toward conducting projects in the information technology field (Al-Dmour et al, 2017). In addition, the results are aligned with previous research that has shown that a concept mapping approach can enhance students' attitudes toward learning different topics in different fields including circular and rotational motion in physics (Luchembe et al, 2017), and vocabulary acquisition in language learning (Khoshsima et al, 2016).…”
Section: Participants' Attitudessupporting
confidence: 87%
“…Some studies have reported positive effects of the use of concept mapping on students' attitudes and motivations for conducting computing projects. For instance, reference (Al-Dmour, Gasaymeh, Abuhelaleh, & Almi'ani, 2017) examined the effect of the concept mapping approach on undergraduate information technology students' attitudes and motivations towards documenting a computing capstone project. The results showed that the use of concept mapping as a tool to support student learning had a positive influence on their attitudes and motivations The researchers found that the use of the concept mapping instructional approach to prepare students to conduct a computing project enhanced their communication of their ideas related to the project, helped them in understanding the structure of the project, and improved their motivation and attitudes towards conducting the project.…”
Section: Study Backgroundmentioning
confidence: 99%
See 1 more Smart Citation